2020
DOI: 10.1177/0300060520931259
|View full text |Cite
|
Sign up to set email alerts
|

Effect of preservation time of formalin-fixed paraffin-embedded tissues on extractable DNA and RNA quantity

Abstract: Objectives This study aimed to investigate the factors affecting the quantity of DNA and RNA extractable from human formalin-fixed paraffin-embedded (FFPE) tissues stored for different lengths of time. Methods We randomly selected 20 FFPE specimens harvested from hysteromyoma patients with uterine fibroids during 2010, 2015, and 2017 at the Department of Pathology, Jiading District Central Hospital Affiliated Shanghai University of Medicine and Health Sciences. DNA and RNA extractions were performed using a DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 19 publications
(24 reference statements)
3
18
0
Order By: Relevance
“…Most of the results of our systematic review consisted in articles and reports on Asian population. This is consistent with the major prevalence of EGFR genomic alteration in NSCLC Asian patients [114,115]. Notable, Asian patients appeared to display better response comparing to Caucasian cohorts (see Table 2); this finding shows racial differences in genetic pathways and prompts further studies on this field of research.…”
Section: Discussionsupporting
confidence: 81%
“…Most of the results of our systematic review consisted in articles and reports on Asian population. This is consistent with the major prevalence of EGFR genomic alteration in NSCLC Asian patients [114,115]. Notable, Asian patients appeared to display better response comparing to Caucasian cohorts (see Table 2); this finding shows racial differences in genetic pathways and prompts further studies on this field of research.…”
Section: Discussionsupporting
confidence: 81%
“…This method can be used for long-term storage from 1 month up to 5 years, at room temperature. According to Yi (2020), the paraffin-embedded tissue preservation method did not show any significant difference in extracted DNA and RNA purity as compared to the other method. Further, small-sized extracted DNA fragments were successfully amplified from most paraffin block samples for several years at room temperature (Nam et al 2014).…”
Section: Introductionmentioning
confidence: 84%
“…Thus far, FFPE tissue archives in most African forensic pathology departments have been an underexploited resource for conducting large retrospective and prospective genetic epidemiological studies. 14 , 15 , 16 It is time to utilise these resources at our disposal to the advantage of the African population. The most significant benefit of post-mortem molecular testing is the high disease-specific diagnostic, therapeutic, and prognostic benefits derivable from subsequent genetic analysis.…”
Section: Recommendationsmentioning
confidence: 99%
“… 9 , 11 , 12 , 13 Although blood collected in ethylenediaminetetraacetic acid or fresh frozen tissue samples are the best source of DNA and the preferred material used for genetic testing, numerous studies have reported on the successful use of FFPE tissue samples. 2 , 14 , 15 The successful use of FFPE tissue samples is particularly encouraging because African forensic pathology still faces the dire reality of inadequate funding and resource allocation required to maintain freezer preservation systems for routine collection and storage of blood or tissue samples. 15 , 16 , 17 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation